PENGARUH MODEL PEMBELAJARAN MATCHING PAIRS DAN QUANTUM LEARNING TERHADAP HASIL BELAJAR SISWA SDIT AL-HASAN PADA MATA PELAJARAN PKN KELAS II - SALMAN (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
This research aims to compare the effectiveness of using matching pairs and quantum learning learning models in improving the learning outcomes of class II students at SDIT Al-Hasan, Kota Bangun, Kampar in PKN subjects. The type of research used was two group experiments, namely the group that used the matching pairs learning model and the group that used the quantum learning model. The population in this study were all class II students at SDIT Al-Hasan, Kota Bangun, Kampar, with samples taken randomly and simply. The data was obtained and analyzed using descriptive statistics and t-test to test differences in learning outcomes between the two groups. The results of the research show that there is a significant difference in learning outcomes between students who learn using the matching pairs model and students who learn using quantum learning. After being given treatment, in the posttest, the average score of the matching pairs group increased to 88.57 with a standard deviation of 3.920, while the quantum learning group had an average score of 86.37 with a standard deviation of 8.011. The matching pairs model has proven to be more effective in improving student learning outcomes compared to the quantum learning model. The implication of this research is that the matching pairs model can be considered as an alternative strategy in effective learning to improve student learning outcomes in PKN subjects in class II SDIT Al-Hasan, Kota Bangun, Kampar.